Circular battery design: investing in sustainability and profitability - Wolf, Andreas; Nagler, Felix; Daubinger, Philip; Neef, Christoph; Mandel, Karl; Flegler, Andreas; Giffin, Guinevere A. (Energy and Environmental Science, 2024)
Sustainability along the battery value chain is a much talked about goal but currently comes third after cost and performance. Historically, improved sustainability comes with a penalty in terms of cost and performance. This interplay will certainly evolve in the coming years. Ecological and social aspects driven by legislative frameworks guarantee recycling of lithium-ion batteries (LIBs) to prevent hazardous waste in landfills. The trend in the electric vehicle (EV) sector towards low-cost chemistries like lithium iron phosphate (LFP) represents a double-edged sword, as the recycling profitability of such materials is extremely low for the established recycling methods. Extending battery lifetime and enabling direct recycling, where anode and cathode materials maintain their structure and functionality, are key strategies to increase sustainability and profitability. However, their implementation necessitates a shift in LIB design priorities. This Perspective highlights design for circularity as an enabler for improved battery longevity and direct recycling and represents a key tipping element for reducing cost and increasing sustainability in LIB production and disposition concurrently. We outline challenges and opportunities in battery production with special focus on the European EV sector and define actions required from various stakeholders along the value chain to overcome the mindset of linear economies.
CRIS-Team Scopus Importer:2024-10-25